A study to assess functional outcome of cemented and uncemented total hip replacement in a tertiary care center - Shah, Kunal Ajitkumar; Desai, Mohan Madhav (International Journal of Research in Orthopaedics, 2019)
Background: Total hip replacement (THR) is the most successful and cost effective treatment with aim of pain relief and functional rehabilitation for hip disorders. As the implant designs of THR have evolved over time, the functional outcome and survivorship has improved. Even after so many advancements, it remains unclear that which implants are better, uncemented or cemented. Hence, we took up this study to analyze which of the uncemented or cemented THR have better functional outcome. Methods: This was a longitudinal study conducted during 2014 to 2018. Hundred cases were randomized into groups of 50 each. All patients with age between 55-80 years in whom THR was indicated were included in the study. Uncemented THR was done in Group A and cemented THR was done in Group B. Patients were followed up at 12 weeks, 6 months, 12 months, and 3 years. At follow-up, functional examination in terms of visual analogue scale (VAS) score and Harris hip score (HHS) was done. Results: The mean age of patients in Group A (uncemented) and Group B (cemented) was 62.5 years and 60 years respectively. We found that the difference of VAS score and HHS between Group A and B was statistically significant at 12 weeks and 6 months. The difference of VAS and HHS scores between Group A and B at 12 months and 3 years was not significant. Conclusions: We conclude that cemented THR has better functional outcome at short term. They are cost effective option at age ≥55-60 years.